Pengaruh NPF, FDR, CAR dan Inflasi terhadap Penyaluran Pembiayaan Modal Kerja pada BPRS di Indonesia - Hasna Rohmatunnisa; Leni Nur Pratiwi (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This research aims to analyze how the independent variables of Non Performing Financing, Financing to Deposit Ratio, Capital Adequacy Ratio, and Inflation impact for the Distribution of Working Capital Financing. Data analysis method is multiple regression analysis, data obtained by monthly reports from Islamic Banking Statistics which published by Indonesia Financial Service Authority (OJK) and Inflation data which published by Indonesia Bank period Jan 2014 until Dec 2018 with the total of 58 data samples. The result of this research shows that Non Performing Financing (NPF) has a significant positif linear effect on Working Capital Financing, Financing to Deposit Ratio (FDR) and Capital Adequacy Ratio (CAR) have significant negative linear effects on Working Capital Financing, while Inflasi had no effect on Working Capital Financing. Concurrently, all the variables have significant effects on Working Capital Financing.